2019
DOI: 10.1536/ihj.19-258
|View full text |Cite
|
Sign up to set email alerts
|

Appetite Predicts Clinical Outcomes in High Risk Patients Undergoing Trans-Femoral TAVI

Abstract: Transcatheter aortic valve implantation (TAVI) has been recognized as a standard therapy for severe aortic valve stenosis. However, since some patients who receive TAVI have poor outcomes, the predictors of clinical outcomes after TAVI are important. The aim of this study was to investigate the association between appetite and long-term clinical outcomes. We screened consecutive cases who received TAVI at our medical center between July 2014 and October 2018. A total of 139 patients who received transfemoral T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[33] Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission. [34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 74%
“…[33] Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission. [34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 74%
“…Staniute et al further also demonstrated that anxiety, depression and social support can indirectly affect the quality of life of patients with HF [38]. Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission [39][40][41][42]. Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cutoff value by ROC curve [43] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure [44].…”
Section: Discussionmentioning
confidence: 95%
“…[38] Moreover, anxiety, appetite and sleep were con rmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status in uences the risk of readmission. [39][40][41][42] Kitamura M not only con rmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [43] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [44] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [45] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these ndings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 86%